PENGARUH SHOPPING LIFE STYLE, FASHION INVOLVEMENT DAN SALES PROMOTION TERHADAP IMPULSE BUYING PADA TOKO THREE SECOND JALAN SOEKARNO HATTA MALANG - Kholikuddin Amrulloh; N. Rachma; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to analyze the effect of Shopping Life Style, Fashion Involvement and Sales Promotion on Impulse Buying at the Three Second shop in Soekarno Hatta Malang. This research is quantitative research. The sampling method used is purporsive sampling. There is a population of 2,700 respondents and a sample of 96 respondents was obtained. The analysis used is multiple linear regression. The results in this study indicate that simultaneous Shopping Life Style, Fashion Involvement and Sales Promotion have a significant effect on Impulse Buying. And partial Shopping Life Style on the coefficients table is 0.639 so that there is no significant effect on Impulse Buying, Fashion Involvement in the coeffisients table is 0.000 so that it has a significant effect on Impulse Buying and Sales Promotion on the coefficient table. significant effect on Impulse Buying.